On Psychoses, Conspiracies, Creative Flow and the Absent-Mindedness of Genius: An Evolutionary Function-Dysfunction Taxonomy of the Multiple Subjective Realities of the Human Mind - Persson, Roland S. (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2021)
The significance of illusion as a positive force in everyday life has been underestimated in both societal discourse and in empirical science. The objective of this study is to provide a synthesis of many academic disciplines’ understanding of illusion and reality by proposing a taxonomy of functional and dysfunctional subjective realities as based on the assumption that the human mind is adaptive in an evolutionary sense and likely to be a quantum entanglement system. Assumptions and discussions needed to construct the taxonomy are generally based on empirical research drawing from evolutionary theory, neurology, biology, anthropology, psychology, psychiatry, physics and other disciplines. The purpose of the proposed taxonomy is heuristic, serving as a base for further studies drawing particular attention to the fact that, by evolutionary processes, Homo sapiens have been made dependent on multiple subjective realities where illusion and reality are not necessarily opposites. The article is concluded by discussing possible reasons for why illusions as a positive force in human behaviour has been neglected in comparison to the dysfunctions of the human mind of which research abound.